From Impairment to Disability: Exploring Social Constructs in Cristina Henriquez’s The Book of Unknown Americans - Chaudhary, Hamna Imran; Hanif , Zahra (Journal of Research in Humanities, 2024)
The research study investigates the concepts of impairment and disability, and identifies techniques employed by capitalism to produce disability in the society by analyzing Cristina Henriquez’s The Book of Unknown Americans through the lens of Marxist Disability Studies. In the light of the framework presented by Michael Oliver, the research paper inspects as to how impairment is a biological deficiency and disability is a social construct, in order to explore the ways by which the society renders an able individual as disable. The research challenges the established belief about disability being a problem of the body and delves into the social model. It aims to highlight how the capitalist power structure builds its capital through human exploitation and various other means, which ultimately creates disability in society. The paper inquiries about the impacts of capitalism through the analysis of characters in the novel. This research is delimited to a character study in the light of the themes of Marxism and Disability Studies; the characters and situations pertaining to this sphere are intricately analyzed through Michael Oliver’s theoretical framework, paving way for institutions to understand the exploitative measures exercised by the capitalist power structure to produce disability in the society. This research arises at the conclusion that the capitalist structure indeed paves a path for suppressing the people with disabilities.